Factors affecting variability in feedlot steer profits - Michael R. Langemeier; J. Mintert; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1992)
This study examined the relative importance of price and animal performance factors on cattle finishing profitability. Using data from a single feedlot, sale prices, feeder prices, and corn prices explained 90 to 95% of the variation in steer profits. About 50% of the variability was explained by fed cattle prices alone. Because sale, feeder, and corn prices have a large impact on profits per head, cattle feeders should attempt to manage the risks associated with these three factors.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Cattle finishing profitability; Sale prices; Feeder cattle prices